P204 A retrospective study of home non-invasive ventilation for patients with severe COPD in a regional centre. (December 2018) - Harbord, P; Ewles, S; Cull, F; Gibson, D; Wilkinson, J; Dushianthan, A; Sivaloganathan, A
Abstract : Introduction and objectives: COPD is associated with significant morbidity and mortality. Home non-invasive ventilation (NIV) is thought to offer some benefit to patients in chronic ventilatory failure, although its use remains controversial. 1 The primary outcome of this study is to evaluate exacerbation frequency requiring hospitalisation following initiation of domiciliary NIV. Method: This is a retrospective study of COPD patients receiving domiciliary NIV in Wessex. Data were collected from patients' notes and available electronic databases. Comparison between groups was assessed by Student's T-Test. Results: 59 patients were identified with an average age of 64 years (range 42–83). 42% had co-existing diagnoses e.g. obstructive sleep apnoea (OSA) or obesity hypoventilation syndrome (OHS). Patients had severe COPD (FEV1 of 30% predicted). 32 patients (54%) started NIV as an inpatient. NIV usage on average was optimal with a minimum of 7.68 hours per night. Following the initiation of domiciliary NIV, there were improvements in arterial pH, PaCO2 and oxygenation. There was a 45% relative risk reduction in COPD related hospitalisations at 24 months following the initiation of domiciliary NIV (p=0.0006). Conclusion: Our data show a significant reduction in the frequency of COPD related hospitalisations post initiation of domiciliary NIV. These results are consistent with the findings from a recent randomised control trial. 2 Ongoing data collection is required to assess the impact of this intervention on long term mortality. References: Dretzke J, et al. International Journal of COPD 2016;11:2269–86. Murphy PB, et al. JAMA2017;317:2177–218.